2020
DOI: 10.3171/2019.11.spine19978
|View full text |Cite
|
Sign up to set email alerts
|

Influence of comorbid knee osteoarthritis on surgical outcome and sagittal spinopelvic/lower-extremity alignment in elderly patients with degenerative lumbar spondylolisthesis undergoing transforaminal lumbar interbody fusion

Abstract: OBJECTIVEThis retrospective study aimed to clarify the influence of comorbid severe knee osteoarthritis (KOA) on surgical outcome in terms of sagittal spinopelvic/lower-extremity alignment in elderly patients with degenerative lumbar spondylolisthesis (DLS).METHODSIn total, 110 patients aged at least 65 years (27 men, 83 women; mean age 74.0 years) who underwent short-segment lumbar fusion were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The pelvic morphology, which is influenced by sagittal malalignment, was significantly different in elderly patients with concurrent KOA and degenerative LSDs compared to patients with LSD only [ 18 ]. Increased sagittal malalignment with a lack of LL was caused by double-level listhesis (i.e., spondylolisthesis and/or retrolisthesis) and greater knee flexion [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pelvic morphology, which is influenced by sagittal malalignment, was significantly different in elderly patients with concurrent KOA and degenerative LSDs compared to patients with LSD only [ 18 ]. Increased sagittal malalignment with a lack of LL was caused by double-level listhesis (i.e., spondylolisthesis and/or retrolisthesis) and greater knee flexion [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although decompression with short-segment fusion at less than three levels can yield improvement of clinical outcomes, corrective lumbar surgery alone may be insufficient for radiological outcomes because of greater pelvic retroversion (high PT) and, worse sagittal spinopelvic alignment [ 20 , 21 ]. Kohno et al reported that surgical strategies in concurrent degenerative knee and LSDs may be necessary to restore sagittal spinopelvic alignment, followed by decreased pelvic retroversion [ 18 ]. In our study, patients with preoperative TKA exhibited greater pelvic retroversion than patients with KOA, and more often required fusion surgery for correction of sagittal spinopelvic alignment.…”
Section: Discussionmentioning
confidence: 99%
“…A further 75 studies were excluded at the second stage screening (full text), mainly because the study aims were not related to the research question, both conditions were not explored, and non-peer reviewed publications, such as conference proceedings, comments, and research notes. Twelve studies 4,5,8,13,21,28,29,30,31,32,33,34 were therefore included into the nal analysis of the current review (Table 1).…”
Section: Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Poor global alignment negatively impacts the alignment of the lower extremities. Sagittal malalignment with pelvic retroversion affected knee OA via the effect on knee flexion contracture [ 10 ], which has been recognized to induce cartilage degeneration [ 16 ]. However, the effect of pelvic retroversion on the outcomes of OWHTO is still unclear.…”
Section: Introductionmentioning
confidence: 99%